2017
DOI: 10.5603/kp.a2017.0072
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with omega-3 acids after myocardial infarction and modification of inflammatory markers in light of the patients’ diet: a preliminary study

Abstract: A b s t r a c tBackground: Neuroendocrine activation, activation of proinflammatory cytokines and platelets, and endothelial dysfunction play a significant role in the development of heart failure (HF). Aim:The aim of the work was to assess the effect of supplementation with EPA and DHA in a daily dose of 1 g on selected inflammatory markers and platelet activation in patients with HF after recent myocardial infarction in light of their diet. Methods:This preliminary study was a randomised, double-blind trial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
(26 reference statements)
0
8
0
2
Order By: Relevance
“…EPA has been widely tested for its benefits as a dietary supplement or as neoadjuvant therapy in cancer because of its anti-inflammatory qualities and safe toxicity profile 2123 . However, it has never been considered a mainstream approach in cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…EPA has been widely tested for its benefits as a dietary supplement or as neoadjuvant therapy in cancer because of its anti-inflammatory qualities and safe toxicity profile 2123 . However, it has never been considered a mainstream approach in cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Long-chain polyunsaturated fatty acids (PUFAs) and their derivatives can modulate many metabolic and inflammatory pathways in diabetic and nondiabetic subjects [ 15 19 ]. Epidemiological evidence has indicated that populations with high fish consumption had less risk of diabetes and ASCVD [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of dietary fiber deficiency in patients with CHF and the anti-inflammatory properties of prebiotic doses of lactulose have been observed. 46,47 One of the promising research directions is the probiotics influence on the metabolic pathways through which the gut microbes can effect on the host organism. For example, the TMAO production decrease can be achieved by blocking the enzyme choline-TMA-lyase, which converts choline to TMA.…”
Section: Possibilities Of Intestinal Microflora Modulations In Chronic Heart Failurementioning
confidence: 99%